Recent Progress of Nanostructured Sensing Materials from 0D to 3D: Overview of Structure–Property‐Application Relationship for Gas Sensors. Issue 9 (15th August 2021) - Zhou, Tingting; Zhang, Tong
Abstract: Along with the progress of nanoscience and nanotechnology, nanomaterials with attractive structural and functional properties have gained more attention than ever before, especially in the field of electronic sensors. In recent years, the gas sensing devices have made great achievement and also created wide application prospects, which leads to a new wave of research for designing advanced sensing materials. There is no doubt that the characteristics are highly governed by the sensitive layers. For this reason, important advances for the outstanding, novel sensing materials with different dimensional structures including 0D, 1D, 2D, and 3D are reported and summarized systematically. The sensing materials cover noble metals, metal oxide semiconductors, carbon nanomaterials, metal dichalcogenides, g‐C3 N4, MXenes, and complex composites. Discussion is also extended to the relation between sensing performances and their structure, electronic properties, and surface chemistry. In addition, some gas sensing related applications are also highlighted, including environment monitoring, breath analysis, food quality and safety, and flexible wearable electronics, from current situation and the facing challenges to the future research perspectives. Abstract : A comprehensive overview of recent progress on gas sensors based on various functional materials varying from 0D to 3D is provided. The multifunctional sensing applications, including environmental monitoring, breath analysis, food quality and safety, and flexible, wearable electronics are summarized. In addition, the recent development and further challenge are also discussed and highlighted.